New algorithms for numerical solution of nonlinear integro-differential equations of third order using haar wavelets - Fayyaz , M.; Azram, Mohammad (Sci.Int.(Lahore), 2013)
This paper deals with the extension of earlier work [3] (designed for Fredholm and Voltera integral equations), [16] (designed for Fredholm and Voltera integro-differential equations of first-order) and [4] (designed for Fredholm and Voltera integro-differential equations of second-order) to third-order nonlinear Fredholm as well as nonlinear Voltera integro-differential equations. The approach used in this paper make use of hidden valuable dimensions of Haar wavelets. The proposed method provides strong generic ground, thus yielding solution of both Fredholm and Volterra integro-differential equations of third-order and second kind. Four numerical examples are used to illustrate the accuracy of the proposed method.